Neuroprotective Effects of Oligosaccharides From Periplaneta Americana on Parkinson's Disease Models In Vitro and In Vivo - Miao-Miao Liu; Nan Zhou; Na Jiang; Kai-Min Lu; Kai-Min Lu; Chuan-Fang Wu; Jin-Ku Bao (Frontiers Media S.A., 2022)
Parkinson's disease (PD) is one of the neurodegenerative diseases that is characterized by obvious motor and some nonmotor symptoms. Various therapeutics failed in the effective treatment of PD because of impaired neurological function in the brain and various complications. Periplaneta Americana oligosaccharides (OPA), the main active ingredients extracted from the medicine residues of Periplaneta Americana (P. Americana), have been reported to exert anti-inflammatory effects. The purpose of this study was to evaluate the possible mechanisms of OPA against 1-methyl-4-phenylpyridinium (MPP+)-induced apotosis in SH-SY5Y cells and its potential neuroprotective effects in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD subacute model mice. The data demonstrated that OPA significantly reversed the MPP+-induced decrease in SH-SY5Y cell viability, reduced the proportion of apoptotic cells, and protected SH-SY5Y cells from apoptosis in a dose-dependent manner by regulating the expression of apoptosis-related genes. Furthermore, OPA also alleviated the motor dysfunction of PD model mice, prevented the loss of tyrosine hydroxylase positive cells, suppressed the apoptosis of substantia nigra cells, and improved the dysbiosis of gut microbiota in vivo, suggesting that OPA demonstrated a significantly neuroprotective effect on PD model mice. These results indicated that OPA might be the possibility of PD therapeutics with economic utility and high safety.